PELATIHAN ANALISIS DATA MODEL MILES DAN HUBERMAN UNTUK RISET AKUNTANSI BUDAYA - Thalib, Mohamad Anwar (Madani: Jurnal Pengabdian Ilmiah, 2022)
This training comes from starting many accounting research based on local wisdom values. This is also in line with the interest of the Islamic Accounting Department students to study culture-based accounting research. However, this interest is still constrained by their shared understanding of data analysis to explore cultural accounting research. This training aims to increase students' knowledge of Islamic Accounting majors on the Miles and Huberman model data analysis for cultural accounting research. This training was divided into four stages; pre-test, material explanation, illustration of data analysis in cultural accounting research, and post-test. The training results showed an increase in students' understanding of Miles and Huberman's data analysis models for cultural accounting research. This increase in performance could be seen through the post-test results of the participants showing a higher score than the pre-test results.